Improvement of Obesity Events Through Online Fast Food Dating Patterns at University X Students in Depok City - Yasmin Az Zahrah; Liya Arista (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
The fast-food online diet can outweigh obesity. The research was conducted on students because students were at the stage of adulthood where metabolism slows down and the trend of ordering food online is mostly done by students. This study identified the relationship between fast food online diet, physical activity, and genetic history with obesity. The research design used was cross sectional with a population of all University X students class 2016-2019 and a total sample of 164 respondents. Data obtained from the FFQ and IPAQ questionnaire sheets through the online G-form. The results of the bivariate analysis with the Chi-Square test showed that there was no significant relationship between online fast food eating patterns and BMI / obesity (p> 0.005), likewise for physical activity variables also did not show a significant relationship with obesity (p = 0.746) However, for genetic history, there was a significant association with obesity (p